Enhancing Public Awareness about the Impact of Boycotts on Purchasing Decisions for Vaseline Products - Dewi, Suci Ananda; Rokan, Mustafa Khamal; Nurlaila, Nurlaila (Universitas Islam Negeri Sumatera Utara, 2024)
This article discusses the impact of boycotts on Vaseline products triggered by the Israel-Palestine conflict and the strategies that can be applied to address this issue. The prolonged conflict in Gaza and international support for Palestine have spurred boycott movements, including in Indonesia, as reflected in the Fatwa of the Indonesian Ulema Council (MUI). The primary focus of this research is on the methods of outreach and collaboration in managing the impact of boycotts on Vaseline products. The outreach method aims to educate both the company and consumers about the effects of boycotts and effective communication strategies. Collaboration with influencers and communities helps the company improve its brand image and strengthen its relationship with consumers. The results of this outreach indicate that while the company and consumers have gained a better understanding, strategic steps are still needed to improve brand image and effectively manage the impact of the boycott. The decline in sales and Unilever's stock price, which includes Vaseline products, highlights the tangible effects of the boycott, emphasizing the importance of communication strategies and positive campaigns to restore brand reputation and boost consumer trust